Emergence of whole-cell MALDI-MS biotyping for high-throughput bioanalysis of mammalian cells?. (April 2013) - Munteanu, Bogdan; Hopf, Carsten
Since their inception in the 1970s, methods for classification of microorganisms based on mass spectral fingerprints obtained by MALDI-TOF MS have become a mainstay in environmental as well as in clinical microbiology. Recently, related whole-cell MALDI-TOF fingerprinting workflows have been adopted for the classification of mammalian cells. In this report we summarize this work and discuss the challenges of adapting whole-cell MS fingerprinting methods for the successful classification of mammalian cells. We highlight current limitations as well as opportunities and emerging applications of this technology in industrial and clinical settings, such as cell-line authentication, clinical diagnostics, and quality and productivity control in bioprocesses.